Extensive genetic heterogeneity and molecular characteristics of emerging astroviruses causing fatal gout in goslings - Hao Cui; Xinhao Mu; Xin Xu; Jun Ji; Ke Ma; Chaoliang Leng; Lunguang Yao; Yunchao Kan; Yingzuo Bi; Qingmei Xie (Poultry Science, 2022)
ABSTRACT: Since 2017, outbreaks of gosling astroviruses (GoAstV) causing the major symptoms related to gout in geese have posed a threat to China's poultry industry and caused huge economic losses. In this study, tissue samples from goslings with gout and urate deposition as the main symptoms were taken from 14 goose farms in different regions of China and screened for pathogen infection. The infection rate of GoAstV was 100%, whereas the infection rates of goose parvovirus, reovirus, Tembusu virus, and goose hemorrhagic polyomavirus were 2, 4, 0, and 0%, respectively. In total, 14 GoAstV strains were isolated and their complete genomes were sequenced. Based on the phylogenetic trees, the 14 isolated strains were classified as GoAstV (G-I) and were considered distant from strains belonging to GoAstV (G-II). The multiple sequence alignments indicated a tremendous amount of amino acid mutations in some parts of the encoding proteins of these strains; the main mutations were located in open reading frames (ORFs)—ORF1a and ORF2, such as M533V and F568S in ORF1a and A614T in ORF2. On the other hand, Further, 2 of the 14 GoAstV strains were possibly derived through inter-GoAstV-I recombination. Taken together, these findings indicate that GoAstVs are evolving in a more complex manner and have diverse transmission routes.